Avaliação da intenção de realizar mamografia como subsídio para ações na promoção da saúde - Sousa, Francisco Stélio de (2010)
Recognizing the magnitude of the public health problem that breast cancer has become over the years and considering mammography as specific procedure for early detection, mammography screening was elected as desired behavior for this investigation. The aim was to assess the behavioral intention and its determinants to perform mammography screening among women in a rural community, with or without a persuasive message. This is an experimental study, only-posterior type, and the Theory of Planned Behavior was a theoretical and methodological framework. The study was conducted in a city of Paraiba, with a sample of 148 women divided into experimental groups 70 (47.3%) and Control 78 (52.7%). The participants were, mostly, married women with incomplete primary education, work at home, catholic, with monthly incomes up to 2 minimum wages, aged 35 to 78 years. The data collect was performed in two steps: a survey of beliefs (n = 33) in October/2009 and assessment of intention and its determinants in November/2009. Beliefs composed the questions formulated in semantic differential scales of bipolar adjectives Likert type. The data were analyzed comparing the two groups, being tested by Fisher-Freeman-Halton, Mann-Whitney test and correlation coefficient of Spearman. It was used the procedure for Forward logistic regression, Wald test, Hosmer-Lemeshow and Omnibus, in addition to R2 Nagelkerke for predictive power. The analysis used the software PASW 18.0 and R version 2.8.1, with a significance level of 5%. The modal salient behavioral beliefs positive were breast cancer prevention, early diagnosis and itself care, and the negatives were pain and fear. Most frequent normative beliefs were physician, television, neighbor and friend. As facilitating factors, were most often cited: referent, money, availability of the examination in SUS and ease of marking. Among the impediments were taking so long to check / perform the examination and lack of money. Attitude was positive in both groups, however the control group showed better performance. The higher scores of subjective norm were presented by the experimental group, with predominance of the item that assessed whether most people thought that the participant should perform the mammogram in the next three months (p = 0.000). The referent with significant statistically were: physician, mother, sister, nurse and community agents. Regarding the behavioral control perception, the experimental group (79.34) had better performance comparing to the control group (70.15). The measure of behavioral intention received positive trend in both groups, with the mean of the experimental group (81.92) bigger than the control group (67.84). The predictor variables that best explained the intention were the attitude and subjective norm, with coefficient of determination of approximately 50% (R2 = 0.503). Knowledge of behavioral intentions should improve the strategies development of nursing work and other health professionals, like shares of health education to awaken women to the importance of mammography screening and make possible active search for women of appropriate ages to perform exams for early detection.